Nutritional Status of Pregnant Women Aged Less Than 20 Years is a Risk Factor For The Incidence of Babies With Low Birth Weight (LBW) - Asti Melani Astari Astari; Ayut Merdikawati; Muladefi Choiriyah; Helmi Nindra Agustin (Indonesian Journal of Human Nutrition, 2022)
Low birth weight (LBW) is influenced by various factors, such as maternal education, gestational age, maternal nutritional status, and economic level. The high pregnancy rate in adolescent mothers is in line with pregnancy complications experienced, one of which is giving birth to LBW babies. The aim of this study was to analyze the risk factors most associated with the incidence of LBW babies in mothers aged less than 20 years old in Wagir District, Malang Regency. The data collection method was used cross-sectional. The inclusion criteria in this study were mothers who were less than 20 years old, had given birth to a baby with LBW, and were domiciled in Wagir District. The data was analysed by logistic regression test. A total of 106 respondents participated in this study. The results showed that the factors that were significantly related were nutritional status (p-value 0.012), economic level (p-value 0.030), and gestational age (p-value 0.046). The dominant factor was nutritional status (p-value 0,012; OR 0,666). Nutritional status is the most influential thing for the health of both mother and baby, so the role of health workers in educating women during the preconception period regarding nutrition and the risk of pregnancy is essential.